Role of Psychological Disorder and Depression in Job Performance Based on the Teacher-Apprentice System - Kai CUI, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Various studies examined the role of psychological factors among employees. However, the effect of personality disorder and depression was not examined on job performance. Therefore, the objective of this study is to examine the role of personality disorder and depression in job performance. This investigation was carried out among the employees of Chinese retail stores. To examine the relationship between personality disorder, depression, work efficiency, and job performance, a survey was carried out among the retail stores. 700 questionnaires were distributed by using the cluster sampling technique. Data were analyzed by using Smart PLS. It is found that psychological factors have a significant effect on job performance. Any case of personality disorder has a negative role in job performance. Personality disorder has a negative effect on work efficiency. Moreover, depression also has a negative effect on job performance. Depression shows a negative role to decrease work efficiency. Therefore, both psychological factors, including; personality disorder and depression have a negative effect on job performance.